Why play outside? Problematising outdoor play as a biopedagogical task. Issue 1 (2nd January 2017) - Robinson, Daniel B.; Barrett, Joe
ABSTRACT: Although outdoor play has been widely recognised for the many benefits it affords children, some have rationalised the need for it based on goals related to physical health. More specifically, these instrumental goals have been closely related to obesity, overweight, and/or physical (in)activity. Adhering to obesity discourses and the notion of a childhood obesity epidemic, such instrumentalisation of outdoor play unnecessarily positions it as a biopedagogical task. Herein we have identified three relatively recent and notable institutes of truth that perpetuate this instrumentalisation of play into a biopedagogical task. Through our consideration and analysis of the initial conception of nature-deficit disorder, subsequent research into outdoor playgrounds and natural play spaces in schools, and a recent national report on physical activity, we hope to initiate and invite candid contemplation, reflection, and critique for and from those within the physical and health education field.